(3GdeSFhdjI GdLfGFjI Yf GdGeJfGY (B: s (3OQGSI ebGQfI Hjf GdTQjYI GdESdGejI hGdbGfhf GdhVYj (B/ s - (3LeGd eMeO SYjO SjOs; (3jhSa eMehO bGSe s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3JJfGhd GdOQGSI GdeSFhdjI GdLfGFjI Yf GdGeJfGY, hgj GdJRGe GdTNU (B( (3GdeeJfY (B) (3HJMed GdfJGFL GdJj QJHgG GdbGfhf Ch GdTQY Ydi GeJfGYg ZjQ GdeTQhY (B. (3h jJab Gdabg GdLfGFj GdESdGej h GdbGfhf GdhVYj aj gPG GdTCf ; EP Jbhe GdLQjeI cCUd YGe HGdJQc Ch GdGeJfGY (B: (3EPG NGda hGLHB bGfhfjB (B: (3Ch NGda CeQB TQYjB (B. (3h GdHMK aj CSGS GdeSFhdjI GdLfGFjI Yf GdGeJfGY gh GdHMK Yf eHQQ deTQhYjI JhbjY GdLRGA Ydi GdeeJfY (B. (3h GdJhUd Edi EbQGQ GdeSGhGI Hjf GdaYd GdEjLGHj h GdGeJfGY aj eLGd GdeSFhdjI GdLfGFjI Ydi hLg GdNUhU(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B523-568.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3fXQjI GdJHYIs; (3LQjeI GdEMLGes; (3GdhGLH GdbGfhfjs; (3GdJQc GdLfGFjs; (3GdeLQe HGdGeJfGYs; (3GeJfGY GdbVGIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs